2016
DOI: 10.19045/bspab.2016.50029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nursery sowing dates, seedling age and nitrogen levels on bulb quality and marketable yield of onion (Allium cepa L.)

Abstract: . Influence of nursery sowing dates, seedling age and nitrogen levels on bulb quality and marketable yield of onion (Allium cepa L. Abstract Research was conducted at Vegetable Research Area, Institute of Horticultural Sciences, University of Agriculture, Faisalabad, to study the Influence of nursery sowing dates, seedling ages and nitrogen levels on bulb quality and marketable yield of onion (Allium cepa. L) var. Pulkara. Seed of onion were sown in two different nurseries, from each nursery seedlings were tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…This might be due to the fact that the optimum date of transplanting planted had better growth, which resulted in higher production of dry matter content of bulb (Sultana, 2015). This result is also consistent with the findings of Muhammad et al (2016) who reported that the seedling transplanted at 60 days have high dry matter percentage as compared to the seedling transplant in early stage and it might be attributed to the fact that as the bulb size decreased quantity of water content also decreased resulting in high percentage of dry matter.…”
Section: Bulb Dry Matter Contentsupporting
confidence: 92%
“…This might be due to the fact that the optimum date of transplanting planted had better growth, which resulted in higher production of dry matter content of bulb (Sultana, 2015). This result is also consistent with the findings of Muhammad et al (2016) who reported that the seedling transplanted at 60 days have high dry matter percentage as compared to the seedling transplant in early stage and it might be attributed to the fact that as the bulb size decreased quantity of water content also decreased resulting in high percentage of dry matter.…”
Section: Bulb Dry Matter Contentsupporting
confidence: 92%
“…This might be due to the fact that the optimum age of seedlings planted had better growth, which resulted in higher production of dry matter content of bulb (Sultana, 2015). This result is also consistent with the findings of Muhammad et al (2016) who reported that the seedling transplanted at 60 days have high dry matter percentage as compared to the seedling transplant in early stage and it might be attributed to the fact that as the bulb size decreased quantity of water content also decreased resulting in high percentage of dry matter. Increasing the rate of phosphorus from nil to 46 kg P 2 O 5 ha -1 not significantly increased the bulb dry matter fraction of onion.…”
Section: Bulb Dry Matter Fractionsupporting
confidence: 92%
“…Dosages of potassium application in comparison with nitrogen and phosphorus was explained earlier [6] and the average NPK levels in onion crop [7]. Results of Tahir et al [8] revealed that nitrogen application significantly affected most of the parameters. Plots treated with Nitrogen 120 kg ha -1 produced maximum bulb diameter (6.82 cm), bulb neck diameter (1.09 cm), bulb fresh weight (141.37 g), bulb dry weight (15.61g) and marketable yield (12.81 ton ha -1 ) with reducing bolting (24.72%).…”
Section: Introductionmentioning
confidence: 84%